A Method for the Acquisition of Formalized Knowledge in Pathology - van Ginneken, Astrid M.; Jansen, W.; Smeulders, A. W. M.; van der Lei, J.; Baak, J. P. A. (Methods of Information in Medicine, 1990)
A tool is introduced for the acquisition of pathology knowledge in a formalized form, directly by the expert. Formalization of the knowledge is intended to make descriptive pathology knowledge more suitable for computerized diagnostic support since a formal representation of knowledge allows more extensive indexing, hence more flexible access. The knowledge acquisition (KA) tool also provides a useful research instrument to investigate to what extent pathology knowledge can be made explicit, to what degree ambiguity is present, in what way experts differ when formalizing knowledge, and whether it is feasible to incrementally acquire decision criteria on the basis of the formalized descriptive knowledge.Crucial in the design of the KA tool is the incorporated meta-knowledge, which is reflected by the knowledge-base structure and is used to elicit knowledge from the expert. Knowledge is acquired from the expert via a menu-driven user interface, which follows the general steps of the pathologist when describing a case. The paper discusses the considerations underlying the design, the implementation of the KA tool, and the research goals.
Keywords: Knowledge Acquisition; Knowledge Formalization; Computer-Assisted Diagnosis; Pathology